Conceptualización y categorización en personas menores expuestas al Programa de Complementación Alimentaria (2012)
ABSTRACT: The purpose of the study was to identify the existence or the absence of major differences in concept formation and categorization in children aged between the ages of 4 and 5, who participated or not in the ‘Dietary Supplementation Program’ delivered through the ‘Plan to Improve Diet and Nutrition in Antioquia’ by the municipality of Envigado, during the years 2006 - 2010. The study was quasi-experimental with a non-equivalent control group. 175 children were evaluated with the sub-scales of the content of the Navarra Oral Language Test. The study found significative differences in scores of categorization and concept formation between those children who participated in the program or those who didn’t Even though both groups demonstrated deficiencies in the development of the variables, the participant group had higher achievements.